Evaluasi Program Pendidikan Karakter Islami Menggunakan Model Goal Oriented Evaluation di Ra Al-Mu’minin Atula - Lina Hardianti; Nurlathifah Thulfitrah B. (Jurnal Pendidikan Dirgantara, 2026)
This study aims to evaluate the implementation of the Islamic Character Education Program at RA Al-Mu’minin Atula using the Goal Oriented Evaluation model. Islamic character education in early childhood education plays a crucial role in shaping students’ religious attitudes, moral values, and noble character through the internalization of Islamic values from an early age. This research employed a qualitative approach with a descriptive research design. Data were collected from the head of the institution, classroom teachers, and students through observation and in-depth interviews. The Goal Oriented Evaluation model was applied to assess the achievement of program objectives by comparing predetermined goals with the actual implementation and outcomes in the field. The findings indicate that the Islamic character education program at RA Al-Mu’minin Atula has been implemented fairly effectively, particularly through routine religious activities such as reciting Iqra before learning sessions, collective prayers, and habituation of discipline and polite behavior. The program positively contributes to the development of students’ religious character. However, several aspects require improvement, especially in formulating more measurable indicators and establishing systematic evaluation documentation. In conclusion, the Goal Oriented Evaluation model is appropriate for evaluating Islamic character education programs in early childhood education institutions and provides valuable recommendations for continuous program improvement.